Silicon nanocrystals embedded in silicon carbide for tandem solar cell applications - Schnabel, M (2015)
Tandem solar cells are potentially much more efficient than the silicon solar cells that currently dominate the market but require materials with different bandgaps. This thesis presents work on silicon nanocrystals (Si-NC) embedded in silicon carbide (SiC), which are expected to have a higher bandgap than bulk Si due to quantum confinement, with a view to using them in the top cell of a tandem cell. The strong photoluminescence (PL) of precursor films used to prepare Si-NC in SiC (Si-NC/SiC) was markedly reduced upon Si-NC formation due to simultaneous out-diffusion of hydrogen that passivated dangling bonds. This cannot be reversed by hydrogenation and leads to weak PL that is due to, and limited by, non-paramagnetic defects, with an estimated quantum yield of ≤5×10-7. Optical interference was identified as a substantial artefact and a method proposed to account for this. Majority carrier transport was found to be Ohmic at all temperatures for a wide range of samples. Hydrogenation decreases dangling bond density and increases conductivity up to 1000 times. The temperature-dependence of conductivity is best described by a combination of extended-state and variable-range hopping transport where the former takes place in the Si nanoclusters. Furthermore, n-type background doping by nitrogen and/or oxygen was identified. In the course of developing processing steps for Si-NC-based tandem cells, a capping layer was developed to prevent oxidation of Si-NC/SiC, and diffusion of boron and phosphorus in nanocrystalline SiC was found to occur via grain boundaries with an activation energy of 5.3±0.4 eV and 4.4±0.7 eV, respectively. Tandem cells with a Si-NC/SiC top cell and bulk Si bottom cell were prepared that exhibited open-circuit voltages Voc of 900 mV and short-circuit current densities of 0.85 mAcm-2. Performance was limited by photocurrent collection in the top cell; however, the Voc obtained demonstrates tandem cell functionality.